RATING THE PERFUSION OF THE LARGE INTESTINE SEGMENT IN PATIENTS WITH A HISTORY OF LAPAROSCOPIC TOTAL MESORECTAL EXCISION - Huseynov, S.A.; Azimov, E.H.; Sultanova, M.J. (World of Medicine and Biology, 2023)
The purpose of the study was to assess the perfusion of the large intestine segment with the angiography in quality and quantity during the laparoscopic total mesorectal excision. The work was carried out on the basis of the analysis of the results of fluorescent images of 28 patients who were diagnosed with adenocarcinoma of the rectum of various degrees and underwent laparoscopic total mesorectal excision. Using the fluorescence curve, T½max and the time ratio (TR=T½ max/T max) from the graphs, the fluorescence intensity of the colon was assessed as weak, medium or high. Of the patients under our supervision, T½max18 sec–in 21.4 % of patients. In 16.7 % of cases in patients with low perfusion (TR